3D-printed biological organs: medical potential and patenting opportunity. (May 2015) - Yoo, Seung-Schik
<x xml:space="preserve">Abstract</x> Three-dimensional (3D) bioprinting has emerged as a new disruptive technology that may address the ever-increasing demand for organ transplants. 3D bioprinting offers many technical features that allow for building functional biological tissue constructs by dispensing the individual or group of cells into specific locations along with various types of bio-scaffold materials and extracellular matrices, and thus, may provide flexibility needed for on-demand individualized construction of biological organs. Several key classes of 3D bioprinting techniques are reviewed, including potential medical and industrial applications. Several unanswered engineering components for the ultimate creation of printed biological organs are also discussed. The complicated nature of the human organs, in addition to the legal and ethical requirements for safe implantation into the human body, would require significant research and development to produce marketable bioprinted organs. This also suggests the possibility for further patenting and licensing opportunities from different sectors of the economy.